1979-80 Report to ILCA Programme Committee - International Livestock Centre for Africa (International Livestock Centre for Africa, 1980)
Summarizes research findings in analysis of the existing systems, i.e. in production monitoring, veterinary survey, ecological monitoring, household economics, socio-economics & aerial surveys, and also in testing of innovations conducted by ILCA's Subhumid Programme in Nigeria and outlines the work envisaged in these respects and also in experimentation & modelling for the future.